IMPACT, INNOVATION, AND CREATIVITY FIELD ECONOMY AND SOCIAL FROM TRANSFORMATION MANAGEMENT IN START-UP BUSINESS (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Management transformation in start-up businesses has become a key element in creating innovation and creativity that affects the economic and social sectors. This article aims to analyze how changes in the managerial structure of start-ups can affect business sustainability, create added value for society, and support the growth of the digital economy. Using a descriptive qualitative method, this research examines various start-up management models that have undergone significant transformations, the obstacles faced, and the solutions implemented. This article also discusses the implementation of strategies, the development of managerial concepts, and the positive impact of these transformations on the business and social ecosystems. This research found that management transformation significantly affects the improvement of operational efficiency, team satisfaction, and the company's social participation. The results of this study are expected to serve as an important reference for start-up practitioners, academics, and policymakers.